Cannabinoid Therapeutics in Chronic Neuropathic Pain: From Animal Research to Human Treatment - Campos, Raquel Maria P.; Aguiar, Andrey F. L.; Paes-Colli, Yolanda; Trindade, Priscila Martins Pinheiro; Ferreira, Bruna K.; de Melo Reis, Ricardo A.; Sampaio, Luzia S. (Frontiers in Physiology, 2021)
Despite the importance of pain as a warning physiological system, chronic neuropathic pain is frequently caused by damage in the nervous system, followed by persistence over a long period, even in the absence of dangerous stimuli or after healing of injuries. Chronic neuropathic pain affects hundreds of millions of adults worldwide, creating a direct impact on quality of life. This pathology has been extensively characterized concerning its cellular and molecular mechanisms, and the endocannabinoid system (eCS) is widely recognized as pivotal in the development of chronic neuropathic pain. Scientific evidence has supported that phyto-, synthetic and endocannabinoids are efficient for pain management, while strong data arise from the therapeutic use of Cannabis-derived products. The use of medicinal Cannabis products is directed towards not only relieving symptoms of chronic pain, but also improving several aspects of patients' welfare. Here, we review the involvement of eCS, along with other cellular and molecular elements, in chronic neuropathic pain pathology and how this system can be targeted for pain management.